EFEKTIVITAS VCT DAN TERAPI WARNA TERHADAP PENGAMBILAN KEPUTUSAN TES HIV DAN PENURUNAN TINGKAT KECEMASAN PADA PASIEN BERISIKO TINGGI HIV - Gita Nirmala Sari (Ikatan Bidan Indonesia (IBI), 2018)
The number of cases of HIV / AIDS in Indonesia in 2014 there were 501 400 cases of HIV / AIDS (NAC, 2014). Most of the people know their condition suddenly without any voluntary testing followed. Risk groups are afraid to do voluntary testing because worried about the consequences to be faced after it was revealed they were HIV positive. Anxiety is associated with a sense of ignorance about HIV so that they are afraid to know the results of such tests. Needed a good anxiety management therapy with a green color. The green color can lead to a sense of comfort, relax, reduce stress, balance, and calm emotions (Kusuma, 2010). The study aims was identified about differences in levels of anxiety and decision-making for HIV testing in patients at high risk of HIV infection before and after VCT and color therapy, analyze the effectiveness of VCT and color. This research method is quantitative research Quasi experimental with pre and post test using the control group. Sampling with purposive sampling, different test analysis by Wilcoxon Signed Rank test and linear regression. Results of the study there are differences in anxiety levels before and after VCT and color therapy in the intervention group (p value: 0.014), there are differences in decision making/ willingness of HIV testing before and after given VCT and color therapy in the intervention group (p value: 0.001). VCT and color therapy affects the willingness of the decision making an HIV test (p value: 0.003) and decreased levels of anxiety (p value: 0.006). The conclusion from this study, there is differences in levels of anxiety and decision-making for HIV testing in patients at high risk of HIV infection before and after VCT and color therapy, VCT and color therapy effective in decision making HIV testing and decrease anxiety levels of patients at high risk of HIV infection in VCT clinic Health Center Care Cakung East Jakarta. Keywords: VCT, color therapy, anxiety, decision making HIV testing